Regions in International Trade - Umiński, Stanisław (De Gruyter, 2021)
The book provides a comprehensive approach to the assessment of the nature of exporting activity, combining well-established theoretical reasoning with empirical evidence, and also signalling important economic policy recommendations. It is suitable for a wide range of recipients ranging from scholars and students to policy-makers or local/regional authorities engaged in the process of designing/implementing regional policies.